Effectiveness of Horizontal Sub-drain for Slope Stability on Crack Soil Using Numerical Model - Putu Tantri Kumala Sari; Indrasurya B. Mochtar; Salisa Chaiyaput (My University, 2023)
Abstract A landslide occurred in the hilly area of Tulakan District, Pacitan, East Java Province, Indonesia. This was due to a period of heavy rain, resulting in a cumulative intensity of over 1000 mm in one month and a maximum daily rainfall exceeding 300 mm. Previous reports have suggested the use of horizontal sub-drains to manage groundwater levels and rainwater seepage to reduce the impact on slope stability. Therefore, this study aimed to determine the effectiveness of horizontal sub-drain as an alternative for managing groundwater and rainwater that seeped into the soil to increase the slope factor of safety by using numerical model. It also considered various factors such as the effect of real-time rainfall over a 30-day period before the landslide, hydraulic conductivity, soil parameter due to cracking and weathering, and the existing groundwater level. The coupled programs SEEP/W and SLOPE/W were used for analyses. The result showed that the horizontal sub-drain only increased the safety factor by less than 2% in the presence of a vertical crack and up to 7.7% with vertical cracks and weak layers in high ground water levels. In addition, this study found that horizontal sub-drains could be more effective in increasing the safety factor up to 11.5% when the rainfall intensity was higher (between 1.41 × 10 –0.5 and 1.85 × 10 –0.7 m/s) and lasted for 14 days. The installation position of the drains, soil conditions, rainfall condition, and contour topography were some of the factors that influenced the effectiveness of the horizontal sub-drains in increasing slope stability.
Keywords: Rainwater Harvesting; Factor of safety; Landslides and related hazards